Fondasi Epistemologi untuk Disiplin Ekonomi Islam: Satu Kajian Awal - Ugi Sugiharto (Universitas Muhammadiyah Yogyakarta, 2005)
Unlike in conventional belief, Islamic epistemology is derived not only from the empirical (indrawi and rational ( aqli) sources, but also from the Divine Revelation (khabari), of which the saying of Allah (God) becomes a fundamental characteristic, along with any conduct, behavior and declaration of the Prophet Muhammad peace be upon him. Rather, the Divine Revelation, which is rejected in conventional epistemology, is placed as the very basic component in Islamic epistemology. As the origin of many Islamic academic disciplines including economics, its shape has been codified since long time ago by Muslim scholars in their treatises, which especially relate to the Islamic system of belief ('agidah).However, economic theories in conventional position, which are rational in character and not in violation with the Islamic precepts, are acceptable and can be used as theories in analyzing human behavior in Islamic economics.